Inhibition of the PI3K/AKT-NF-κB Pathway With Curcumin Enhanced Radiation-Induced Apoptosis in Human Burkitt's Lymphoma - Qiao Qiao; Yuanjun Jiang; Guang Li (Elsevier, 2013)
Abstract.: The phosphatidylinositol-3-kinase (PI3K) / protein kinase B (AKT) signal transduction pathway is commonly misregulated in lymphoma and associated with tumorigenesis and enhanced resistance to radiotherapy. Curcumin has been shown to inhibit the PI3K/AKT signal transduction pathway in several tumor models. In this study, we found that curcumin inhibits constitutive and radiation-induced expression of the PI3K/AKT pathway and its downstream regulator nuclear factor kappaB (NF-κB) in human Burkitt's lymphoma, a high-grade non-Hodgkin's lymphoma (NHL). We further demonstrated that the blockage of radiation-induced activation of the PI3K/AKT pathway and its downstream regulator NF-κB by either curcumin or specific PI3/AKT inhibitors (LY294002 for PI3K or SH-5 for AKT) enhance apoptosis in three human Burkitt's lymphoma cell lines (Namalwa, Ramos, and Raji) that were treated with ionizing radiation. However, no synergic effect on radiation-induced apoptosis was found in the cells co-pretreated with curcumin combined with LY294002 or curcumin combined with SH-5. The results from this study suggest that curcumin might play an important role in radiotherapy of high-grade NHL through inhibition of the PI3K/AKT-dependent NF-κB pathway. Keywords:: Burkitt's lymphoma, curcumin, PI3K/AKT, NF-κB, ionizing radiation